Determination of Nitrogen and Phosphorus Fertilizer Rates for Sorghum (Sorghum bicolor L. Moench) Production in Wag-Lasta, Ethiopia - ashebir, merse mengesha; Sebnie, Workat (International Journal on Food, Agriculture and Natural Resources, 2025)
The decline in soil fertility due to topsoil loss caused by erosion, leaching, and continuous crop residue removal is a major challenge for crop production in the Wag-Lasta areas of Ethiopia. To address this issue, a field experiment was carried out in Lasta and Sekota districts, Eastern Amhara, Ethiopia, during the main rainy season in 2014 and 2016. The purpose of the experiment was to determine the optimal nitrogen and phosphorus fertilizer rates for Sorghum bicolor production. The experiment involved four nitrogen rates (0, 23, 46, 69 kgha-1N) and three phosphorus rates (0, 23, 46 kg kgha-1 P2O5) arranged in a randomized complete block design with three replications in a factorial arrangement. Soil samples were collected from 0–20 cm to determine selected soil properties, and agronomic data were collected following standard procedures. The data were then analyzed using SAS software version 9.0, and significant treatment means were separated using the least significant difference at 5% significance level. The results showed that nitrogen and phosphorus rates significantly affected sorghum yield and yield components at both locations. Specifically, applying 23 kg ha-1 N and 46 kg ha-1 P2O5 increased sorghum yield by 60% compared to the control at Sekota, while 23 kg ha-1 N and 23 kg ha-1 P2O5 gave a 125% yield increment over the control at Lalibela. Therefore, it was recommended to apply 23 kg ha-1 N and 46 kg ha-1 P2O5 for sorghum production in Sekota and 23 kg ha-1 N and 23 kg ha-1 P2O5 in Lalibela.